APPLICATION OF CONVERSATION TECHNIQUES AND SCHEDULED PRAYER ACTIVITIES FOR PATIENTS WITH HALLUCINATIONS - Asep Riyana (Journal of Smart Nursing and Health Science, 2025)
Hallucination is a manifestation of a mental problem, where individuals experience alterations in sensory perception, such as hearing voices, sometimes seeing things, and also feeling sensations, touch, and smell. Patients may experience hallucinations in the form of stimuli where they hear various sounds that practically do not exist, not even human voices. They may hear other voices that correspond to what the patient will later perceive as commanding them to harm themselves, others, or the community. The impact of auditory hallucinations is often accompanied by symptoms of depression and anxiety. The purpose of this scientific paper is to determine the effect of talking therapy and scheduled activities, specifically praying, on the ability to control hallucinations. This qualitative case study was conducted for 5 days, from April 6, 2023, to April 19, 2023. The data from the two respondents were collected using an instrument sheet to assess hallucination symptoms. The results of this case study show a decrease in hallucination symptoms in both respondents, with patient 1's initial score of 9 decreasing to 3, and patient 2's initial score of 13 decreasing to 6. In conclusion, this scientific paper indicates that talking therapy and scheduled activities, specifically praying, have an influence on reducing hallucination symptoms, as well as advice for families to always accompany the implementation of conversation therapy and carry out scheduled activities for patients and for puskesmas to always make regular visits to the community with schizophrenics.